The Influence of Health Education on Adolescents Knowledge of Reproductive Health in the Working Area of the UPTD Munjul Health Center - Siti Nuryawati, Lina; Idaningsih, Ayu; Irawan, Ade Tedi; Fitria, Citra; Azril (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2023)
This study aims to identify adolescents' knowledge about reproductive health before and after health education is carried out in the working area of the UPTD Puskesmas Munjul Majalengka Regency in 2022. This type of research is a quantitative study with one group pre-test and post-test design. The population is 2467 people and the sample in this study is adolescents in the working area of the UPTD Munjul Health Center, Majalengka Regency, as many as 100 people in 2022. Data collection used a questionnaire. The data analysis technique used is the Wilcoxon test. The results showed that the average knowledge of adolescents about reproductive health before being given health education was 60.29% and after being given health education was 80.71%. The results of the hypothesis test with an alpha error rate of 0.05 obtained a value of p <0.05 meaning that there is an effect of health education on adolescent reproductive health knowledge in the working area of the UPTD Munjul Health Center, Majalengka Regency in 2022. It is hoped that health workers can improve health promotion programs such as counseling to adolescents in particular about the importance of reproductive health in order to optimize better adolescent health services.